An ACMT Network of Medical Toxicology Clinics (NMTC): A Proposed Collaboration of Medical Toxicologists to Meet National Emergency Preparedness Needs - Matthew Robert Dernbach; Tyler Lopachin; John W. Downs; Nicholas Nacca; Paul Wax; Ziad Kazzi (Journal of Medical Toxicology, 2026)

How a nocturnal cold front amplified wildfire impacts on near-surface air quality downwind of the second largest US wildfire - Sandip Pal; Matthew Hamel; Hassanpreet Dhaliwal; Diya Das; Danielle Harr; Tyler Danzig; Temple R. Lee; Kiran Menon; Nicholas E. Prince; Matthew Asel; Wesley Burgett (Atmospheric Research, 2026)

Lynch syndrome integrative epidemiology and genetics (LINEAGE): rationale for cohort design - Swati G. Patel; Holli A. Loomans-Kropp; Zachariah H. Foda; Bryson W. Katona; Suzi Birz; Carol A. Burke; Jordan Clawson; Brian Furner; Camille Hochheimer; Elizabeth Magnan; Luigi Ricciardiello; Harminder Singh; et al. (Familial Cancer, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Cognitive Intra-individual Variability in Cognitively Healthy APOE ε4 Carriers, Mild Cognitive Impairment, and Alzheimer’s Disease: a Meta-analysis - Stephen L. Aita; Victor A. Del Bene; Donald L. Knapp; Claire E. Demming; Vasilios C. Ikonomou; Tyler Owen; Ivan A. Campbell; Bailey N. Wagaman; Nicholas C. Borgogna; Joshua E. Caron; Robert M. Roth; Benjamin D. Hill (Neuropsychology Review, 2025)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Precision in Spinal Cord Injury Research: A Novel Electromagnetic Impactor for a Consistent Porcine Model - Leonard Steger; Abdul Karim Ghaith; Carly Weber-Levine; Kayla Robinson; Christina Krueger; Constantin Smit; Siddharth Krishnan; Kelley M. Kempski Leadingham; Daniel Davidar; Denis Routkevitch; Kelly Jiang; Victor Quiroz; et al. (Annals of Biomedical Engineering, 2025)

Correction to: Incremental efficacy systematic review and meta-analysis of psilocybin-for-depression RCTs - Nicholas C. Borgogna; Tyler Owen; Dan Petrovitch; Jacob Vaughn; David A. L. Johnson; Louis A. Pagano; Stephen L. Aita; Benjamin D. Hill (Psychopharmacology, 2025)

Incremental efficacy systematic review and meta-analysis of psilocybin-for-depression RCTs - Nicholas C. Borgogna; Tyler Owen; Dan Petrovitch; Jacob Vaughn; David A. L. Johnson; Louis A. Pagano; Stephen L. Aita; Benjamin D. Hill (Psychopharmacology, 2025)
Rationale Psilocybin is a potentially paradigm-shifting depression intervention. We conducted a systematic review and meta-analysis of psilocybin-for-depression randomized controlled trials (RCTs). Objectives Systematically assess harm reporting, risk of bias, action mechanism specification, and incremental therapeutic effect sizes in the psilocybin-for-depression RCT literature. Methods Assessed databases included PsycINFO, CINAHL, Embase, Medline, Web of Science, and Scopus. Search terms “Psilocybin” or “Psychedelic” were paired with “Depression”, and "Randomized Controlled Trial" or “RCT”. Results We identified k = 9 RCTs ( k = 10 subgroups) involving n = 602 participants (56% psilocybin). Five studies had low/very low harm quality reporting, opposed to two with high. Most studies demonstrated a high risk of bias. Therapeutic mechanisms of action (MoAs) were discussed in varying detail but rarely assessed in original publications. Psilocybin was moderately superior to controls at reducing depression ( g = 0.62; 95% CI = 0.27, 0.98). Effects were heterogenous (τ = .47). Smaller studies evidenced stronger effects that favored psilocybin (Egger’s b 0 = 3.63, p = .014). Almost all studies documented financial conflicts of interests. Conclusion Psilocybin demonstrates significant depression reduction relative to controls. However, researchers, clinicians, and stakeholders should consider several contextual factors. Effects were moderate and attenuated in larger and better-controlled studies. Harms reporting and risk of bias was high, though partly driven by unique challenges of psilocybin research. MoAs were variably specified but rarely assessed; suggesting it is unclear how depression is reduced. We advise researchers conduct RCTs with active control conditions, larger samples, and include MoA assessments. Independent RCTs from researchers without financial conflicts of interest are needed.

The importance of verifying biological activity predictions in metabolomics studies of natural products: A case study on antimicrobial properties of Cannabis sativa (hemp) - Fridah C. Rotich; Joseph B. Mangun; Joëlle Houriet; Warren S. Vidar; Tyler N. Graf; Nicholas H. Oberlies; Nadja B. Cech (Phytochemistry Letters, 2025)

Ecosurveillance reveals subtle metabolic effects on the non-native cane toad (Rhinella marina) from low levels of accumulated environmental per- and polyfluoroalkyl substances - Damian C. Lettoof; Marina Suzuki; Sandra Nilsson; Thao V. Nguyen; Nicholas Bourne; Cassandra L. Pegg; Sally Stockwell; Utpal Bose; Jacob Devine; Tyler Contor; Bruce L. Webber; Anna H. Kaksonen; et al. (Environmental Pollution, 2025)

Safety assessment of protein A and derivation of a parenteral health-based exposure limit - Jessica C. Graham; Sathanandam S. Anand; Joel Bercu; Lauren Besenhofer; Christina de Zafra; Yu Feng; Craig Fisher; Jedd Hillegass; Richard Hutchinson; Robert Jolly; Chandrika Moudgal; Tyler Nicholas; et al. (Regulatory Toxicology and Pharmacology, 2024)

Piloting wastewater-based surveillance of norovirus in England - David I. Walker; Jessica Witt; Wayne Rostant; Robert Burton; Vicki Davison; Jackie Ditchburn; Nicholas Evens; Reg Godwin; Jane Heywood; James A. Lowther; Nancy Peters; Jonathan Porter; et al. (Water Research, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Insights into nearshore sandbar dynamics through process-based numerical and logistic regression modeling - Trenton M. Saunders; Nicholas Cohn; Tyler Hesser (Coastal Engineering, 2024)

fNIRS is capable of distinguishing laterality of lower body contractions - Rob J. MacLennan; Jesus A. Hernandez-Sarabia; Shawn M. Reese; JoCarol E. Shields; Claire M. Smith; Katharina Stute; Jordyn Collyar; Alex A. Olmos; Tyler L. Danielson; Demi L. MacLennan; Jason I. Pagan; Ryan M. Girts; et al. (Experimental Brain Research, 2024)

A model for community-driven development of best practices: the Ocean Observatories Initiative Biogeochemical Sensor Data Best Practices and User Guide - Hilary I. Palevsky; Sophie Clayton; Heather Benway; Mairead Maheigan; Dariia Atamanchuk; Roman Battisti; Jennifer Batryn; Annie Bourbonnais; Ellen M. Briggs; Filipa Carvalho; Alison P. Chase; Rachel Eveleth; et al. (Frontiers in Marine Science, 2024)
The field of oceanography is transitioning from data-poor to data-rich, thanks in part to increased deployment of in-situ platforms and sensors, such as those that instrument the US-funded Ocean Observatories Initiative (OOI). However, generating science-ready data products from these sensors, particularly those making biogeochemical measurements, often requires extensive end-user calibration and validation procedures, which can present a significant barrier. Openly available community-developed and -vetted Best Practices contribute to overcoming such barriers, but collaboratively developing user-friendly Best Practices can be challenging. Here we describe the process undertaken by the NSF-funded OOI Biogeochemical Sensor Data Working Group to develop Best Practices for creating science-ready biogeochemical data products from OOI data, culminating in the publication of the GOOS-endorsed OOI Biogeochemical Sensor Data Best Practices and User Guide. For Best Practices related to ocean observatories, engaging observatory staff is crucial, but having a “user-defined” process ensures the final product addresses user needs. Our process prioritized bringing together a diverse team and creating an inclusive environment where all participants could effectively contribute. Incorporating the perspectives of a wide range of experts and prospective end users through an iterative review process that included “Beta Testers’’ enabled us to produce a final product that combines technical information with a user-friendly structure that illustrates data analysis pipelines via flowcharts and worked examples accompanied by pseudo-code. Our process and its impact on improving the accessibility and utility of the end product provides a roadmap for other groups undertaking similar community-driven activities to develop and disseminate new Ocean Best Practices.

Green Tea Catechins Decrease Solubility of Raloxifene In Vitro and Its Systemic Exposure in Mice - Victoria O. Oyanna; Baron J. Bechtold; Katherine D. Lynch; M. Ridge Call; Tyler N. Graf; Nicholas H. Oberlies; John D. Clarke (Pharmaceutical Research, 2024)

Relationship of mercury and selenium in ocean fish frequently consumed in the Seychelles: A comparison to levels in ocean fish consumed in the US - Grazyna Zareba; Donald Harrington; Tom Scrimale; Aubrey Lesperance; Gene E. Watson; Edwin van Wijngaarden; Conrad F. Shamlaye; Tyler Nicholas; Gary J. Myers; Sally W. Thurston (NeuroToxicology, 2023)

What was old is new again: Phenotypic screening of a unique fungal library yields pyridoxatin, a promising lead against extensively resistant Acinetobacter baumannii (AB5075) - Heather L. Winter; Laura Flores-Bocanegra; Kristóf B. Cank; William J. Crandall; Fridah C. Rotich; Madeline N. Tillman; Daniel A. Todd; Tyler N. Graf; Huzefa A. Raja; Cedric J. Pearce; Nicholas H. Oberlies; Nadja B. Cech (Phytochemistry Letters, 2023)

Paleoecological evidence for environmental specialization in Paranthropus boisei compared to early Homo - Kaedan O'Brien; Nicholas Hebdon; J. Tyler Faith (Journal of Human Evolution, 2023)

Hominoid-specific sulcal variability is related to face perception ability - Benjamin J. Parker; Willa I. Voorhies; Guo Jiahui; Jacob A. Miller; Ethan Willbrand; Tyler Hallock; Nicholas Furl; Lúcia Garrido; Brad Duchaine; Kevin S. Weiner (Brain Structure and Function, 2023)

Genomic erosion in a demographically recovered bird species during conservation rescue - Hazel A. Jackson; Lawrence Percival‐Alwyn; Camilla Ryan; Mohammed F. Albeshr; Luca Venturi; Hernán E. Morales; Thomas C. Mathers; Jonathan Cocker; Samuel A. Speak; Gonzalo G. Accinelli; Tom Barker; Darren Heavens; et al. (Conservation Biology, 2022)
The pink pigeon ( Nesoenas mayeri ) is an endemic species of Mauritius that has made a remarkable recovery after a severe population bottleneck in the 1970s to early 1990s. Prior to this bottleneck, an ex situ population was established from which captive‐bred individuals were released into free‐living subpopulations to increase population size and genetic variation. This conservation rescue led to rapid population recovery to 400–480 individuals, and the species was twice downlisted on the International Union for the Conservation of Nature (IUCN) Red List. We analyzed the impacts of the bottleneck and genetic rescue on neutral genetic variation during and after population recovery (1993–2008) with restriction site‐associated sequencing, microsatellite analyses, and quantitative genetic analysis of studbook data of 1112 birds from zoos in Europe and the United States. We used computer simulations to study the predicted changes in genetic variation and population viability from the past into the future. Genetic variation declined rapidly, despite the population rebound, and the effective population size was approximately an order of magnitude smaller than census size. The species carried a high genetic load of circa 15 lethal equivalents for longevity. Our computer simulations predicted continued inbreeding will likely result in increased expression of deleterious mutations (i.e., a high realized load) and severe inbreeding depression. Without continued conservation actions, it is likely that the pink pigeon will go extinct in the wild within 100 years. Conservation rescue of the pink pigeon has been instrumental in the recovery of the free‐living population. However, further genetic rescue with captive‐bred birds from zoos is required to recover lost variation, reduce expression of harmful deleterious variation, and prevent extinction. The use of genomics and modeling data can inform IUCN assessments of the viability and extinction risk of species, and it helps in assessments of the conservation dependency of populations.

Mapping Seafloor Relative Reflectance and Assessing Coral Reef Morphology with EAARL-B Topobathymetric Lidar Waveforms - Nicholas Wilson; Christopher E. Parrish; Tim Battista; C. Wayne Wright; Bryan Costa; Richard K. Slocum; Jennifer A. Dijkstra; Matthew T. Tyler (Estuaries and Coasts, 2022)
Topobathymetric lidar is becoming an increasingly valuable tool for benthic habitat mapping, enabling safe, efficient data acquisition over coral reefs and other fragile ecosystems. In 2014, a novel topobathymetric lidar system, the Experimental Advanced Airborne Research Lidar-B (EAARL-B), was used to acquire data in priority habitat areas in the U.S. Virgin Islands (USVI), spanning the 0–44-m depth range. In this study, new algorithms and procedures were developed for generating seafloor relative reflectance, along with a suite of shape-based waveform features from EAARL-B. Waveform features were then correlated with percent cover of coral morphologies, domed and branched, and total cover of hard and soft corals. Results show that the EAARL-B can be used to produce useful seafloor relative reflectance mosaics and also that the additional waveform shape-based features contain additional information that may benefit habitat classification—specifically, to aid in distinguishing among hard corals and their coral morphologies, domed and branched. Knowing the spatial extent of changes in coral communities is important to the understanding of resiliency of coral reefs under stress from human impacts.

Agreement of the Apple Watch® and Fitbit Charge® for recording step count and heart rate when exercising in water - Nicholas J. Held; Andrew S. Perrotta; Tyler Mueller; Selina J. Pfoh-MacDonald (Medical & Biological Engineering & Computing, 2022)

Comparative sequencing and SNP marker validation for oat stem rust resistance gene Pg6 in a diverse collection of Avena accessions - Tyler C. Gordon; Yue Jin; Nicholas A. Tinker; Wubishet A. Bekele; Samuel Gale; Harold Bockelman; J. Michael Bonman (Theoretical and Applied Genetics, 2022)
Key message Comparative sequence analysis was used to design a SNP marker that aided in the identification of new sources of oat stem rust resistance. Abstract New races of Puccinia graminis f. sp. avenae ( Pga ) threaten global oat production. An A. strigosa accession known to carry the broadly effective oat stem rust resistance gene, Pg6 , was crossed with two susceptible A. strigosa accessions to generate 198 F 2:3 families and 190 F 5:6 RILs. The RIL population was used to determine that Pg6 was a single dominant gene located between 475 and 491 Mbp on diploid chromosome AA2 of the A. atlantica genome. This region was further refined by identifying SNPs associated with Pg6 resistance in a panel of previously sequenced A-genome accessions. Twenty-four markers were developed from SNPs that showed perfect association between the Pg6 phenotype and 11 sequenced Avena diploid accessions. These markers were validated in the RILs and F 2:3 families, and the markers most closely linked with resistance were tested in a diverse panel of 253 accessions consisting of oat stem rust differentials, all available diploid Avena spp. accessions, and 41 A. vaviloviana accessions from the National Small Grains Collection. One SNP marker located at 483, 439, 497 bp on AA2, designated as AA2_483439497, was perfectly associated with the Pg6 phenotype in Avena strigosa diploids and was within several Kb of a resistance gene analog, RPP13. The marker results and seedling testing against Pga races DBD, KBD, TJS, and TQL enabled the postulation of Pg6 and potential new sources of resistance in the Avena panel. These results will be used to infer Pg6 presence in other germplasm collections and breeding programs and can assist with introgression, gene pyramiding, and cloning of Pg6 .

Marginal support for a trophic cascade among sympatric canids in peripheral wolf range - Nicholas L. Fowler; Todd M. Kautz; Tyler R. Petroelje; Clay M. Wilton; Kenneth F. Kellner; Daniel J. O’Brien; Bill Parsons; Dean E. Beyer; Jerrold L. Belant (Ecology, 2021)
Trophic cascades reportedly structure ecological communities through indirect species interactions. Though the predator–herbivore–autotroph relationship has received much attention, mechanistic evidence supporting intraguild trophic cascades is rare. We established 348 remote camera sites (1 August–5 September 2019) across seven study areas of varying wolf ( Canis lupus ) density including one study area where wolves were absent in northern Michigan, USA. Using multi‐species occupancy modeling at species‐relevant spatial scales, we evaluated the hypothesis that increased wolf occurrence suppresses coyote ( C . latrans ) occurrence with corresponding increased red fox ( Vulpes vulpes ) occurrence mediated by land cover edge density, human presence, and temporal partitioning. Remote cameras recorded >600,000 images and included 6,370, 10,137, and 4,876 detections of wolves, coyotes, and foxes, respectively. Fox occupancy probability was more than three times as high (0.29) at camera sites where wolves were present, relative to sites wolves were absent (0.09). Pairwise species interactions supported expected size‐based dominance patterns among canids and insignificant effects were directionally consistent with reported reduced strength of top‐down effects in peripheral wolf range. Increased edge density also increased co‐occurrence of coyote and wolves, likely a function of increased prey availability and refugia for coyotes. Though foxes occurred in spatial proximity to wolves, competition was limited by greater temporal partitioning than observed between coyotes and foxes that were spatially segregated. Collectively, our results provide marginal support for the reported trophic cascade among wolves, coyotes, and foxes wherein top‐down effects may be reduced near the edge of current wolf distributions. As predators continue to recolonize portions of their historic range, knowledge of the effects on intraguild predators has implications for species management and predicting prey population responses.

Variable Species Responses to Experimental Stony Coral Tissue Loss Disease (SCTLD) Exposure - Sonora S. Meiling; Erinn M. Muller; Danielle Lasseigne; Ashley Rossin; Alex J. Veglia; Nicholas MacKnight; Bradford Dimos; Naomi Huntley; Adrienne M. S. Correa; Tyler Burton Smith; Daniel M. Holstein; Laura D. Mydlarz; et al. (Frontiers in Marine Science, 2021)
Stony coral tissue loss disease (SCTLD) was initially documented in Florida in 2014 and outbreaks with similar characteristics have since appeared in disparate areas throughout the northern Caribbean, causing significant declines in coral communities. SCTLD is characterized by focal or multifocal lesions of denuded skeleton caused by rapid tissue loss and affects at least 22 reef-building species of Caribbean corals. A tissue-loss disease consistent with the case definition of SCTLD was first observed in the U.S. Virgin Islands (USVI) in January of 2019 off the south shore of St. Thomas at Flat Cay. The objective of the present study was to characterize species susceptibility to the disease present in St. Thomas in a controlled laboratory transmission experiment. Fragments of six species of corals ( Colpophyllia natans , Montastraea cavernosa , Orbicella annularis , Porites astreoides , Pseudodiploria strigosa , and Siderastrea siderea ) were simultaneously incubated with (but did not physically contact) SCTLD-affected colonies of Diploria labyrinthiformis and monitored for lesion appearance over an 8 day experimental period. Paired fragments from each corresponding coral genotype were equivalently exposed to apparently healthy colonies of D. labyrinthiformis to serve as controls; none of these fragments developed lesions throughout the experiment. When tissue-loss lesions appeared and progressed in a disease treatment, the affected coral fragment, and its corresponding control genet, were removed and preserved for future analysis. Based on measures including disease prevalence and incidence, relative risk of lesion development, and lesion progression rates, O. annularis, C. natans , and S. siderea showed the greatest susceptibility to SCTLD in the USVI. These species exhibited earlier average development of lesions, higher relative risk of lesion development, greater lesion prevalence, and faster lesion progression rates compared with the other species, some of which are considered to be more susceptible based on field observations (e.g., P. strigosa ). The average transmission rate in the present study was comparable to tank studies in Florida, even though disease donor species differed. Our findings suggest that the tissue loss disease affecting reefs of the USVI has a similar epizootiology to that observed in other regions, particularly Florida.

Behavioural responses of female lake trout Salvelinus namaycush to male chemical stimuli and prostaglandin F 2α - Tyler J. Buchinger; Weiming Li; Nicholas S. Johnson (Journal of Fish Biology, 2020)
Male olfactory cues may guide aggregation on spawning reefs, mate evaluation and synchronized gamete release in lake trout Salvelinus namaycush , but a lack of information on the source and identity of the cues precludes direct tests of their function. Using a two‐channel flume, we found ovulated female lake trout increased time spent in the channel treated with spermiated male‐conditioned water, urine and bile but not synthesized prostaglandin F 2α . We suggest future efforts to characterize male olfactory cues focus on urine and postulate that bile acids contribute to its behavioural activity.

Mapping of the stem rust resistance gene Pg13 in cultivated oat - Aida Z. Kebede; Belayneh Admassu-Yimer; Wubishet A. Bekele; Tyler Gordon; J. Michael Bonman; Ebrahiem Babiker; Yue Jin; Sam Gale; Charlene P. Wight; Nicholas A. Tinker; Jim G. Menzies; Aaron D. Beattie; et al. (Theoretical and Applied Genetics, 2020)

Increased pheromone signaling by small male sea lamprey has distinct effects on female mate search and courtship - Tyler J. Buchinger; Ugo Bussy; Ethan G. Buchinger; Skye D. Fissette; Weiming Li; Nicholas S. Johnson (Behavioral Ecology and Sociobiology, 2017)

Assessment of Damage and Adaptation Strategies for Structures and Infrastructure from Storm Surge and Sea Level Rise for a Coastal Community in Rhode Island, United States - Christopher Small; Tyler Blanpied; Alicia Kauffman; Conor O’Neil; Nicholas Proulx; Mathew Rajacich; Hailey Simpson; Jeffrey White; Malcolm Spaulding; Christopher Baxter; J. Swanson (Journal of Marine Science and Engineering, 2016)
This paper presents an evaluation of inundation, erosion, and wave damage for a coastal community in Rhode Island, USA. A methodology called the Coastal Environmental Risk Index (CERI) was used that incorporates levels of inundation including sea level rise, wave heights using STWAVE, and detailed information about individual structures from an E911 database. This information was input into damage functions developed by the U.S. Army Corps of Engineers following Hurricane Sandy. Damage from erosion was evaluated separately from local published erosion rates. Using CERI, two different adaptation strategies were evaluated that included a combination of dune restoration, protective berms, and a tide gate. A total of 151 out of 708 structures were estimated to be protected from inundation and wave action by the combined measures. More importantly, the use of CERI allowed for the assessment of the impact of different adaptation strategies on both individual structures and an entire community in a Geographical Information Systems (GIS) environment. This tool shows promise for use by coastal managers to assess damage and mitigate risk to coastal communities.

Comparing Chemistry and Census-Based Estimates of Net Ecosystem Calcification on a Rim Reef in Bermuda - Travis A. Courtney; Andreas J. Andersson; Nicholas R. Bates; Andrew Collins; Tyler Cyronak; Samantha J. de Putron; Bradley D. Eyre; Rebecca Garley; Eric J. Hochberg; Rodney Johnson; Sylvia Musielewicz; Tim J. Noyes; et al. (Frontiers in Marine Science, 2016)

Ultraviolet Vision and Avoidance of Power Lines in Birds and Mammals - Nicholas Tyler; Karl‐Arne Stokkan; Chris Hogg; Christian Nellemann; Arnt‐Inge Vistnes; Glen Jeffery (Conservation Biology, 2014)

Feedbacks underlie the resilience of salt marshes and rapid reversal of consumer‐driven die‐off - Andrew H. Altieri; Mark D. Bertness; Tyler C. Coverdale; Eric E. Axelman; Nicholas C. Herrmann; P. Lauren Szathmary (Ecology, 2013)
Understanding ecosystem resilience to human impacts is critical for conservation and restoration. The large‐scale die‐off of New England salt marshes was triggered by overfishing and resulted from decades of runaway crab grazing. In 2009, however, cordgrass began to recover, decreasing die‐off ∼40% by 2010. We used surveys and experiments to test whether plant–substrate feedbacks underlie marsh resilience. Initially, grazer‐generated die‐off swept through the cordgrass, creating exposed, stressful peat banks that inhibited plant growth. This desertification cycle broke when banks eroded and peat transitioned into mud with fewer herbivores, less grazing, and lower physical stress. Cordgrass reestablished in these areas through a feedback where it engineered a recovery zone by further ameliorating physical stresses and facilitating additional revegetation. Our results reveal that feedbacks can play a critical role in rapid, reversible ecosystem shifts associated with human impacts, and that the interplay of facilitative and consumer interactions should be incorporated into resilience theory.

A trophic cascade triggers collapse of a salt‐marsh ecosystem with intensive recreational fishing - Andrew H. Altieri; Mark D. Bertness; Tyler C. Coverdale; Nicholas C. Herrmann; Christine Angelini (Ecology, 2012)
Overexploitation of predators has been linked to the collapse of a growing number of shallow‐water marine ecosystems. However, salt‐marsh ecosystems are often viewed and managed as systems controlled by physical processes, despite recent evidence for herbivore‐driven die‐off of marsh vegetation. Here we use field observations, experiments, and historical records at 14 sites to examine whether the recently reported die‐off of northwestern Atlantic salt marshes is associated with the cascading effects of predator dynamics and intensive recreational fishing activity. We found that the localized depletion of top predators at sites accessible to recreational anglers has triggered the proliferation of herbivorous crabs, which in turn results in runaway consumption of marsh vegetation. This suggests that overfishing may be a general mechanism underlying the consumer‐driven die‐off of salt marshes spreading throughout the western Atlantic. Our findings support the emerging realization that consumers play a dominant role in regulating marine plant communities and can lead to ecosystem collapse when their impacts are amplified by human activities, including recreational fishing.

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

Pacific Rim Forestry - Thomas Brandeis; Olaf Kuegler; Robert Pattison; Örjan Jonsson; James Halperin; Kathleen McGinely; Constance Carpenter; Kathleen Friday; Guy Robertson; Nicklos Dudley; Robert James; Richard Sniezko; et al. (Journal of Forestry, 2011)
68Stakeholders' questions about subtropical and tropical forests can be as diverse and unique as the forests themselves. Obtaining the information needed to begin answering these questions requires innovation and adaptation of existing forest mensuration and inventory techniques that were developed primarily for use in temperate and boreal forests with a strong forest industry presence. Five cycles of forest inventory and monitoring in Puerto Rico and two cycles in the US Virgin Islands under the Forest Inventory and Analysis (FIA) program highlight the commonalities and differences between working in these subtropical forests and the temperate forests of the continental United States. Additionally, the Caribbean implementation of the FIA program has often taken a different approach from that used in the Pacific Islands territories. We can improve on delivery of forest resource information to island stakeholders by studying these experiences. By sharing the lessons learned with other Pacific Rim countries engaging in forest inventory and monitoring, we can learn from each other.

Unravelling contamination signals in biogenic silica oxygen isotope composition: the role of major and trace element geochemistry - Tim S. Brewer; Melanie J. Leng; Anson W. Mackay; Angela L. Lamb; Jonathan J. Tyler; Nicholas G. Marsh (Journal of Quaternary Science, 2008)
The oxygen isotope composition of diatom silica ( δ 18 O diatom ) provides valuable information for palaeoclimate studies where carbonate proxies are either rare or absent in many lakes and ocean sediments. Unfortunately, mineral and rock fragments found alongside diatoms in most sediments can be problematic as the method used will liberate oxygen from all components within the sediment, producing both high‐frequency noise and low‐frequency excursions that can resemble climate signals. Removal of mineral contamination to date has largely relied upon the combination of chemical leaching and physical separation techniques (e.g. sieving, density). This combination can be inefficient and often significant proportions of contaminants are present in the ‘purified’ diatom sample. Using electron optical imaging and whole‐rock geochemistry on previously ‘purified’ diatom samples, a mass balance approach has been developed whereby the types and proportions of residual contaminants are identified. By integrating this information with measured oxygen isotope ratios of the contaminants, it is then possible to remove contamination effects from the δ 18 O diatom record. Contamination effects relating to carbonates, tephra and silt are modelled for cores from Lake Tilo (Ethiopia) and Lake Baikal (Siberia). In both lakes the new modelled δ 18 O diatom curves show less high‐frequency noise, thus enabling better resolution of low‐frequency climate signals. © Natural Environment Research Council (NERC) copyright 2008. Reproduced with the permission of NERC. Published by John Wiley & Sons Ltd.

Where clocks are redundant: weak circadian mechanisms in reindeer living under polar photic conditions - Bob E. H. van Oort; Nicholas J. C. Tyler; Menno P. Gerkema; Lars Folkow; Karl-Arne Stokkan (The Science of Nature, 2007)